Effects of inclination angle and confining pressure on triaxial unloading-induced slip behaviors of shale fractures - Liu, Yi; Li, Zihan; Zhao, Shisen; Jiang, Jian; Yuan, Chao (Frontiers in Earth Science, 2024)
To explore the effects of fracture inclination angle θ and confining pressure σ3t on the slip behaviors and friction properties of fractures, the triaxial unloading-induced slip experiments were performed on the shale fractures. The results show that the σ3t controls the slip modes of fractures, while the θ affects the occurrence of the stick-slip events during the quasi-static slip stage. With the increase in σ3t, the main slip modes of fracture transform from the stable-slip to stick-slip, and eventually to the creep-slip. The increase in θ facilitated the occurrence of stick-slip events. As the θ increased from 30° to 50°, the number of stick-slip events increased from 0 to 3 and from 2 to 4 for σ3t = 10 MPa and 20 MPa, respectively. For σ3t = 40 MPa, no stick-slip event occurred in the slipping process. The θ and σ3t have great effects on interaction modes between asperities, which directly affected the friction properties of fractures. With increasing σ3t, the void spaces between the asperities were further compacted, resulting in the transition of asperity interaction from overriding mode to shear-off mode. The transition of asperity interaction model therefore brought about the weakening of friction coefficient at the activation point and the onset of dynamic slip stage. There is a competitive relationship between the θ and σ3t for the evolution of the friction properties of fractures. As the θ increase from 30° to 50°, for σ3t = 10 MPa, the mean sheared-off thickness decreased from 0.502 mm to 0.433 mm, while for σ3t = 40 MPa, the mean sheared-off thickness decreased from 0.505 mm to 0.319 mm. With the increment of θ, the anisotropy of joint roughness coefficient was weakened. We suggested that by adjusting the fracturing angle of hydro-fracturing, the earthquakes with large seismic moments may be effectively mitigated.